Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.omtn.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

RNAa and Vector-Mediated Overexpression of DIRAS1 Suppresses Tumor Growth and Migration in Renal Cell Carcinoma

Abstract: The downregulation of DIRAS1 has been suggested to potentially contribute to tumor development and progression in several human cancers. However, the role of DIRAS1 in renal cell carcinoma (RCC) remains elusive. In this study, we examined the DIRAS1 expression level in RCC cell lines and tissues. Both RNA activation (RNAa) and vector transfection methods were used to upregulate the expression of DIRAS1 in RCC cells. Expression analysis revealed that DIRAS1 was significantly downregulated in RCC cell lines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Functionally, several studies showed that DIRAS-1 acts as a potential tumor suppressor by inhibiting cell proliferation and cell viability in different types of cancer, such as renal cell carcinoma, colorectal cancer, murine ovarian cancer cells, and esophageal squamous cell carcinoma, as well as gliomas [2,[4][5][6] and that DIRAS-1 can also suppress tumor growth in nude mice [7]. However, we did not observe an impact of DIRAS-1 overexpression on cell proliferation in the two glioma cell lines analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functionally, several studies showed that DIRAS-1 acts as a potential tumor suppressor by inhibiting cell proliferation and cell viability in different types of cancer, such as renal cell carcinoma, colorectal cancer, murine ovarian cancer cells, and esophageal squamous cell carcinoma, as well as gliomas [2,[4][5][6] and that DIRAS-1 can also suppress tumor growth in nude mice [7]. However, we did not observe an impact of DIRAS-1 overexpression on cell proliferation in the two glioma cell lines analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The DIRAS-1 gene is also known as Rig (Ras-related inhibitor of cell growth) and is located on chromosome band 19p13.3, whereas the DIRAS-2 gene is located on chromosome band 9q22.2 [1,2]. DIRAS-1, in contrast to common oncogenic small GTPases like Ras or Rho family members [3], has been reported as a potential tumor suppressor in human glioblastoma [2], colorectal cancer [4], renal cell carcinoma [5], and ovarian cancer [6], and reduced expression of DIRAS-1 predicts poor prognosis in esophageal squamous cell carcinoma [7]. Bergom and colleagues more closely analyzed the tumor suppressive mechanisms of DIRAS-1 and showed that DIRAS-1 binds to the noncanonical guanine nucleotide exchange factor SmgGDS (Rap1 GTPase-GDP dissociation stimulator 1 = RAP1GDS1) and acts similarly to a dominant-negative small GTPase [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was performed as previously reported [ 16 ], with the following primary immunoblotting antibodies: anti-GAPDH ((10494-1-AP, Proteintech) and anti-ARNTL2 (ab221557, abcam). After transfection with RNA duplex (50 nM) for 24 h, 786-O or Caki-1 cells were performed colony formation and wound healing assay as previously reported [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…DIRAS1 contributed to repressed colony formation and cell activities in ESCC [20]. DIRAS1 silencing facilitated tumor growth, augmented cancer cell survival and metastasis, and suppressed apoptosis [34]. In conclusion, DIRAS1 depletion partially annulled the promotive effect of LINC00261 on EC cell radiosensitivity.…”
Section: Discussionmentioning
confidence: 83%